2018
DOI: 10.1186/s13071-018-3225-6
|View full text |Cite
|
Sign up to set email alerts
|

Polyomic tools for an emerging livestock parasite, the rumen fluke Calicophoron daubneyi; identifying shifts in rumen functionality

Abstract: BackgroundDiseases caused by parasitic flatworms of rumen tissues (paramphistomosis) are a significant threat to global food security as a cause of morbidity and mortality in ruminant livestock in subtropical and tropical climates. Calicophoron daubneyi is currently the only paramphistome species commonly infecting ruminant livestock in temperate European climates. However, recorded incidences of C. daubneyi infection in European livestock have been increasing over the last decade. Whilst clinical paramphistom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…matrixofscience.com) was used for analysis by carrying out an MS/MS ion search, settings were set for the enzyme trypsinallowing 2 missed cleavages, with a fixed modification of carbamidomethyl (C) and a variable modification of oxidation (M) with a peptide charge of 2+, 3+ and 4+. Each sample was then searched against an in-house database composed of a transcript for C. daubneyi (Huson et al, 2018) available to search at https:// sequenceserver.ibers.aber.ac.uk/. Each of the contigs returned were then searched within an in-house copy of the transcript and the nucleotide sequence recorded.…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…matrixofscience.com) was used for analysis by carrying out an MS/MS ion search, settings were set for the enzyme trypsinallowing 2 missed cleavages, with a fixed modification of carbamidomethyl (C) and a variable modification of oxidation (M) with a peptide charge of 2+, 3+ and 4+. Each sample was then searched against an in-house database composed of a transcript for C. daubneyi (Huson et al, 2018) available to search at https:// sequenceserver.ibers.aber.ac.uk/. Each of the contigs returned were then searched within an in-house copy of the transcript and the nucleotide sequence recorded.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Paramphistomes, commonly known as rumen fluke, have been found to infect ruminant animals worldwide (Huson et al, 2017;Huson et al, 2018). Within tropical and sub-tropical regions, rumen fluke infections cause significant production losses; yet only in recent years have rumen fluke infections been observed throughout Europe with the major species responsible confirmed as Calicophoron daubneyi (Sanabria and Romero, 2008;Jones et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This revealed that HDM transcripts were more highly expressed in the NEJ and immature stages Table S3). Of these, 272 proteins were unique to the Transcriptome data is currently available for two paramphistome species, Paramphistomum cervi and C. daubneyi (53,54). However, these studies have been limited to the adult life-cycle stage which are often described as "well-tolerated" by their ruminant hosts since they are responsible for chronic paramphistomosis which is largely subclinical (13).…”
Section: Daubneyi Expresses Orthologues Of Helminth Immunomodulatomentioning
confidence: 99%
“…Nonetheless, acute disease can cause high mortality in both sheep and cattle;3,4 histopathology has demonstrated a localised inflammatory response at the site of attachment in the rumen;5 and in vitro models suggest that the presence of adult flukes may alter ruminal volatile fatty acid production 6…”
Section: Small Ruminantsmentioning
confidence: 99%